Kenya's running tribe - Manners, J.
This article is about a tribe in Kenya that has a remarkable faculty for turning out world class distance runners. The people are called the Kalenjin. They occupy an area about the size of Wales and they number something under 3 million, or about 10 % of Kenya's population. But this group has earned about 75% of Kenya's distance running honors. That number is impressive enough, in view of the degree to which Kenya now dominates the sport, but looked at another way, the figures are even more remarkable: over the past 10 years, athletes from this small tribe have won close to 40% of all the biggest international honors available in men's distance running. Most of this article will be a discussion of various notions that have been advanced to account for this phenomenon, but before going into that I want to throw out a few more numbers to show what I mean by that 40% figure. First, I want to make it clear that I am talking about men's distance running. Kalenjin women - African women in general - have lagged behind their male counterparts for reasons I am afraid I will not have time to get into.